Language policies and language education in Brazil and Canada: an interview with Professor Schmidt - Ferraz, Daniel (Papéis: Revista do Programa de Pós-Graduação em Estudos de Linguagens - UFMS, 2020)
This interview with Prof. Dr. Clea Schmidt from the University of Manitoba presents some of Dr. Schmidt’s and Dr. Ferraz’s perspectives in relation to language education and teacher education in Canada and Brazil. The conversation focuses on essential topics to be problematized by language educators from both countries: neoconservative politics, neoliberalism, plurilingualism, immigration, LGBTQ, pedagogical practices, language policies, and teacher education.